KONTRIBUSI ISLAM DALAM PERADABAN DUNIA - Ariesta Setyawati; Siti Nurislamiah; Hasim Hasim; Rosbandi Rosbandi; Layyinatus Syifa (ISLAMIKA, 2023)
This article describes the important roles of Ibnu Sina and Al-Razi in the development of science and medicine in the medieval Islamic world. Ibnu Sina was known as a polymath who combined philosophy, medicine and natural sciene. His most famous work, ???Kitab Al-Qanun fi al-Tibb???, became a reference work in medicine and philosophy that was very influential. Al-Razi, meanwhile, was an accomplished physician-scientist. His work, ???Kitab ak-Hawi ???, was one of the first medical encyclopedias in history that combined knowledge from Greek, Persian and Arabic cultures. This article will review Al-Razi???s discoveries and contributions in the fields of medicine, chemistry and pharmacology. It will provide a deeper understanding of the role of Ibnu Sina and Al-Razi in the history of Islamic science and medicine and how their contributions are still relevant in the development of modern science.